PENGARUH MEDIA SEMPOA TERHADAP KEMAMPUAN OPERASI HITUNG PENGURANGAN SISWA KELAS II MI - Akhmad Aji Pradana; Jazilatul Ummah (PREMIERE : Journal of Islamic Elementary Education, 2020)
Many students don’t like math. This dislike makes students not very familiar with subtraction calculation operations, thus making the students’ ability to calculate subtraction operations is still low in completing subtraction count operations. Based on the background of the problem, this study is expected to provide answers to the formulation of the problem “How is the influence of the abacus media on the ability to calculate the reduction of second grade students at MI Islamiyah Mulyoagung Singgahan Tuban 2019/2020?”. Based on the formulation of the problem, this study aims “To describe the effect of abacus media on the ability to count reduction operations in grade II students at MI Islamiyah Mulyoagung Singgahan Tuban 2019/2020”. This research uses Quasi Experiment method with quantitative approach through independent sample t test analysis technique. Data collection methods in this study used observation, tests and documentation. The data obtained were analyzed using descriptive analysis then clarified with tables and graphs. The subject of this research is MI Islamiyah Mulyoagung Singgahan Tuban with samples according to the population of 34 students and the sampling technique used was random sampling technique. From the results of the study it can be concluded that tcount = 3.882 and ttable = 1.693. This means that tcount> ttable so that it can be concluded that there is an influence of the use of abacus media on the ability to calculate grade II student reduction operations at MI Islamiyah Mulyoagung. Increased ability to count reduction operations is influenced by the use of abacus media. This is evidenced from the average value of pretest and posttest. Before the experimental group was given a tretment the average pretest value obtained was 69 in the medium category, and after being given a treatment the posttest average value was 81.76 in the high category. While the control group obtained an average pretest value of 68 in the moderate category and because the control group was not given an average treatment of the posttest obtained by 68.82 in the moderate category.